Teachers’ Attitude And Teaching Practices Towards Entrepreneurial Skills: An Exploratory Study On Middle School Science Teachers Of Sindh Province, Pakistan - Nisar, Pashmina (2024)
There is an increasing demand for entrepreneurial skills. The World Economic Forum has established that the majority of the work activities will be automated by the year 2055, creating more complex roles and challenges for future employees. As there is a rise in the number of unsuccessful employees in Pakistan, that is a concern about introducing entrepreneurial skills at the school level. In the case of Pakistan, entrepreneurial skills are emphasized as one of the significant aspects of the middle-level curriculum. However, in schools, particularly in government schools, students are lacking entrepreneurial skills. Science is considered one of the pivotal subjects to develop students’ entrepreneurial skills. The interrelation of entrepreneurial skills and science education in this study portrays the associative nature of both areas. This study accentuates that students with a strong background of scientific knowledge and a solid grasp of entrepreneurial skills are more well-equipped for the demands of the modern world workforce and can enliven innovative ideas. In fulfilling these responsibilities, a teacher should hence have entrepreneurial essence and skills. The attitude and teaching practices of science teachers reflect their entrepreneurial skills. For the purpose of exploring the attitudes and teaching practices of science teachers, this study adopted a qualitative exploratory research approach. An exploratory design enables active participation of the participants, allowing them to generate new knowledge. A purposive sampling approach was employed in selecting the 14 participants who fulfilled the criteria.